Implementation of the Value of Regional Unity through Effective Communication to the Young Generation in Improving the National Resilience of the Republic of Indonesia - Hendrayani, Yani (Pancasila International Journal of Applied Social Science, 2023)
The young generation as the backbone of the nation must realize the various challenges and threats to the nation and then unite and work together to maintain the safety of the nation and state. This should be realized by various parties in Indonesia. It should be taken into consideration to maximize the role of the youth as the generation that will carry the safety of this nation.In the process of conveying knowledge ideas and messages of national insight, the right approach technique is needed. In the communication strategy, the content of the message certainly determines the effectiveness of communication. With this, it is very important to be able to communicate effectively through a communication design that is seriously engineered as a panacea for the young generation's mentality of love for their homeland. In addition, many factors influence the communication process to be successful, so that conveying national insight becomes more interesting both verbally and non-verbally. Among other things, by involving language that is easily understood by the younger generation through facial expressions and vocalizations that arouse enthusiasm to listen to the messages conveyed, which are complemented by forms of games, symbols, photos and films. Seeing the lessons that can be learned from other nations that movies are very effective for spreading nationalism. can initiate patriotic themes that are in accordance with the development of the current era. Cooperation with producers and creative workers can be considered to develop ideas that are of interest to the Indonesian audience.